Reliability, Validity and Responsiveness of the Slovenian Version of the Patient Evaluation Measure (PEM-Slo) in Patients with Wrist and Hand Disorders - BOJNEC Vida; LONZARIĆ Dragan; KLARER REBEC Živa (Sciendo, 2023)
The Patient Evaluation Measure (PEM) is a region-specific patient reported outcome measure (PROM) for hand and wrist disorders, first introduced in English for patients with hand surgery in 1995. The purpose of the study was to assess the psychometric properties of the translated and cross-culturally adapted Slovenian version of PEM (PEM-Slo).